PEMILIHAN STRATEGI PERAWATAN MESIN DI PT XYZ - Simatupang, Lenny Marlina; Susanti, Elva (Computer Science and Industrial Engineering, 2021)
PT XYZ has several production machine units which as part of the manufacturing industry experience problems with the machine maintenance system that has been set by the company which are not carried out by maintenance operators, which causes machines to often experience breakdowns and the production process stops. One solution to this problem is to improve the way in which machine maintenance strategies are chosen. Therefore, this study aims to determine a machine maintenance strategy by involving PT XYZ. The results of this study obtained 3 criteria for selecting and evaluating the criteria for preventive maintenance, predictive maintenance and corrective maintenance with a total of 9 combined sub-criteria. The highest criterion weight is preventive maintenance (1.00), while the highest sub-criteria is time (1.00).